2019
DOI: 10.3390/molecules24081618
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Potent and Selective Halogen-Substituted Imidazole-Thiosemicarbazides for Inhibition of Toxoplasma gondii Growth In Vitro via Structure-Based Design

Abstract: Employing a simple synthetic protocol, a series of highly effective halogen-substituted imidazole-thiosemicarbazides with anti-Toxoplasma gondii effects against the RH tachyzoites, much better than sulfadiazine, were obtained (IC50s 10.30—113.45 µg/mL vs. ~2721.45 µg/mL). The most potent of them, 12, 13, and 15, blocked the in vitro proliferation of T. gondii more potently than trimethoprim (IC50 12.13 µg/mL), as well. The results of lipophilicity studies collectively suggest that logP would be a rate-limiting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 31 publications
(35 reference statements)
1
29
0
Order By: Relevance
“…Recently [ 25 ], we published a new series of halophenyl-substituted imidazole thiosemicarbazides with much better and selective anti- Toxoplasma effects than sulfadiazine (IC 50s 10.30–113.45, selectivity index SI 3.15–19.16, vs. 2721.45 μg/mL, SI < 0.92). Moreover, the most potent of them inhibited tachyzoites proliferation more potently and more selectively than trimethoprim (IC 50 12.13 μg/mL, SI > 2.64) and more potently than sulfadiazine in combination with trimethoprim (IC 50 37.15 μg/mL).…”
Section: Introductionmentioning
confidence: 99%
“…Recently [ 25 ], we published a new series of halophenyl-substituted imidazole thiosemicarbazides with much better and selective anti- Toxoplasma effects than sulfadiazine (IC 50s 10.30–113.45, selectivity index SI 3.15–19.16, vs. 2721.45 μg/mL, SI < 0.92). Moreover, the most potent of them inhibited tachyzoites proliferation more potently and more selectively than trimethoprim (IC 50 12.13 μg/mL, SI > 2.64) and more potently than sulfadiazine in combination with trimethoprim (IC 50 37.15 μg/mL).…”
Section: Introductionmentioning
confidence: 99%
“…Hitherto, our research group identified thiazolidine-chlorophenylhydrazone hybrids with antiproliferative activity comparable to that of irinotecan [17] and thiazolidine-thiohydantoin and thiazolidine-chlorophenylthiosemicarbazone hybrids with antibacterial activity comparable to that of cefuroxime [18,19]. The results of the latest research work [20,21,22] in the field of inhibitory activity of thiosemicarbazide derivatives against protozoan T. gondii , identified that in particular those compounds which in position 4 contain halogen(alkyl)phenyl group are characterized by antiparasitic activity much more advantageous than the commonly used drug sulfadiazine (IC 50 25.67–68.18 μM vs. 10,873.71 μM). These results prompted us to start a pilot synthesis of a series of thiazolidin-4-one derivatives containing in their structure the above-mentioned a thiosemicarbazide moiety (shown in red in Figure 1) to confirm (or exclude) their inhibitory potential against T. gondii tachyzoites; from our research to date, it appears that, although there are objective indications of anti-toxoplasmic activity for the proposed group of compounds, strengthened by reports by Góes and colleagues [14,15,16], in practice these compounds may be quite significantly different in bioactivity or even inactive.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of compounds and drugs on T. gondii proliferation was described in our previous work [20,21,22]. Due to the fact that T. gondii is an intracellular parasite and host cells should not be destroyed by the cytotoxic concentration of compounds, to determine the initial dose of each compound to antiparasitic study CC 30 value was calculated (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…In our laboratory, we obtained earlier and evaluated some thiosemicarbazides with good activity towards T. gondii [ 21 , 22 ]. Continuing in this direction, we designed and obtained thiosemicarbazide derivatives having a nitroimidazole substituent found in Metronidazole—the popular available antiparasitic drug.…”
Section: Introductionmentioning
confidence: 99%